ANALISIS WAKTU SET-UP GANTI DIE MESIN EXTRUDER DSW-2 DENGAN METODE STOPWATCH TIME STUDY DI PT GTR - Santoso, Priyono Budi; Firmansyah, Daffa Aji; Fauzi, Ahmad (Jurnal Sains Ilmu Teknologi Industri, 2024)
PT GTR is a tire manufacturing company for vehicles that has very diverse products so that it often replaces the die to produce one of the components that make up the tire, namely the sidewall. In the die replacement process, there is a work element for setting RPM, which is known to require a short time, so that it can affect the speed of service and these activities, including those that cause loss time. Die replacement set-up activities are included in activities that need to be reduced so that companies can increase customer satisfaction through speed of service. Based on the results of observations using the stopwatch time study method, it was found that the cycle time for the die change set-up activity and the highest RPM setting activity was on the DSW-2 engine with a total cycle time of 4 minutes 46 seconds and 31.53 seconds. Through this research, improvements were made to the working elements of the RPM setting so that the time for set-up changing the die can be reduced by making an auto recipe program for setting RPM with a barcode system. Based on the auto recipe program for the made RPM settings, it was found that the cycle time, normal time, and standard time savings were obtained respectively for the die change set-up activity, namely 45.03 seconds, 46.38 seconds, and 54.73 seconds as well as time savings on the RPM setting work element. of 28.70 seconds.